# Matrix polynomial

In mathematics, a matrix polynomial is a polynomial with square matrices as variables. Given an ordinary, scalar-valued polynomial

${\displaystyle P(x)=\sum _{i=0}^{n}{a_{i}x^{i}}=a_{0}+a_{1}x+a_{2}x^{2}+\cdots +a_{n}x^{n},}$

this polynomial evaluated at a matrix A is

${\displaystyle P(A)=\sum _{i=0}^{n}{a_{i}A^{i}}=a_{0}I+a_{1}A+a_{2}A^{2}+\cdots +a_{n}A^{n},}$

where I is the identity matrix.[1]

A matrix polynomial equation is an equality between two matrix polynomials, which holds for the specific matrices in question. A matrix polynomial identity is a matrix polynomial equation which holds for all matrices A in a specified matrix ring Mn(R).

## Characteristic and minimal polynomial

The characteristic polynomial of a matrix A is a scalar-valued polynomial, defined by ${\displaystyle p_{A}(t)=\det \left(tI-A\right)}$. The Cayley–Hamilton theorem states that if this polynomial is viewed as a matrix polynomial and evaluated at the matrix A itself, the result is the zero matrix: ${\displaystyle p_{A}(A)=0}$. The characteristic polynomial is thus a polynomial which annihilates A.

There is a unique monic polynomial of minimal degree which annihilates A; this polynomial is the minimal polynomial. Any polynomial which annihilates A (such as the characteristic polynomial) is a multiple of the minimal polynomial.[2]

It follows that given two polynomials P and Q, we have ${\displaystyle P(A)=Q(A)}$ if and only if

${\displaystyle P^{(j)}(\lambda _{i})=Q^{(j)}(\lambda _{i})\qquad {\text{for }}j=0,\ldots ,n_{i}-1{\text{ and }}i=1,\ldots ,s,}$

where ${\displaystyle P^{(j)}}$ denotes the jth derivative of P and ${\displaystyle \lambda _{1},\dots ,\lambda _{s}}$ are the eigenvalues of A with corresponding indices ${\displaystyle n_{1},\dots ,n_{s}}$ (the index of an eigenvalue is the size of its largest Jordan block).[3]

## Matrix geometrical series

Matrix polynomials can be used to sum a matrix geometrical series as one would an ordinary geometric series,

${\displaystyle S=I+A+A^{2}+\cdots +A^{n}}$
${\displaystyle AS=A+A^{2}+A^{3}+\cdots +A^{n+1}}$
${\displaystyle (I-A)S=S-AS=I-A^{n+1}}$
${\displaystyle S=(I-A)^{-1}(I-A^{n+1})}$

If I − A is nonsingular one can evaluate the expression for the sum S.